Directory of national focal points for the advancement of women in Asia and the Pacific. - United Nations. Economic and Social Commission for Asia and the Pacific (New York United Nations Economic and Social Commission for Asia and the Pacific, 1993)
An updated edition of the 1989 2nd edition, it includes information from 35 countries showing each country's national focal points and other organization involved. The directory provides information on all organizations, institution and groups including their address, status, year established legal authority, objectives and functions, major activities, publications, staff, budget, and organizational structure. This information is compiled to facilitate exchange of information, experience, and expertise on women-in-development issues in the region and thereby promote technical cooperation among ESCAP members and associate members.
Keywords: Women in development -- Societies, etc. -- Asia -- Directories; Women in development -- Societies, etc. -- Oceania -- Directories; Women in development -- Societies, etc. -- Australasia -- Directories